SOME GENERAL NUMERICAL RADIUS INEQUALITIES FOR THE OFF-DIAGONAL PARTS OF 2 × 2 OPERATOR MATRICES - Bani-Domi, Watheq (Italian Journal of Pure and Applied Mathematics, 2015)
We give some sharp inequalities involving powers of the numerical radii for the oﬀ-diagonal parts of 2 × 2 operator matrices. These inequalities, which are based on some classical convexity inequalities for the nonnegative real numbers, generalize earlier numerical radius inequalities.